2020
DOI: 10.1080/13543784.2020.1709822
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II parallel double-blind randomized controlled clinical trial of perispinal etanercept for chronic stroke: improved mobility and pain alleviation

Abstract: Phase I/II parallel double-blind randomized controlled clinical trial of perispinal etanercept for chronic stroke: improved mobility and pain alleviation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 81 publications
0
39
0
Order By: Relevance
“…Also, TNF inhibitors hold promise as candidate therapies in ischemic stroke. Peri-spinal administration of the non-selective TNF antagonist etanercept provided benefits for post-stroke pain and improved cognitive dysfunction in chronic stroke patients [50,60], demonstrating the potential of anti-TNF inhibitors as antiinflammatory treatment in ischemic stroke. A major barrier to the efficacy of etanercept as a TNF inhibitor in ischemic stroke, however, is its poor blood-brain barrier (BBB) permeability due to its large size.…”
Section: Discussionmentioning
confidence: 99%
“…Also, TNF inhibitors hold promise as candidate therapies in ischemic stroke. Peri-spinal administration of the non-selective TNF antagonist etanercept provided benefits for post-stroke pain and improved cognitive dysfunction in chronic stroke patients [50,60], demonstrating the potential of anti-TNF inhibitors as antiinflammatory treatment in ischemic stroke. A major barrier to the efficacy of etanercept as a TNF inhibitor in ischemic stroke, however, is its poor blood-brain barrier (BBB) permeability due to its large size.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, systemic entanercept adminstration was able to penetrate the contused brain tissue reducing the brain contents of TNF-α, and also stimulated newly formed neuronogenesis [ 255 , 256 ]. Clinically, perispinal administration of etanercept (PSE) has shown early promising results in several studies investigating its effects in neurological recovery and chronic pain post-brain injury [ 257 , 258 , 259 , 260 ]. An observational study investigating the role of PSE in chronic management of TBI and stroke patients reported significant improvements of chronic neurological dysfunctions.…”
Section: Inflammationmentioning
confidence: 99%
“…Etanercept, a selective tumor necrosis factor (TNF) inhibitor, is also a promising strategy targeting neurotoxic immune response. In a Phase I/II clinical trial, peri-spinal administration of etanercept significantly improved mobility function in chronic stroke patients ( 123 ). In addition to inhibiting inflammatory processes, boosting beneficial anti-inflammatory processes also shows a positive role in recovery.…”
Section: Therapeutic Strategies Targeting Brain–peripheral Immune Cromentioning
confidence: 99%